Penciptaan Jiwa dari Sudut Ilmu Tafsir dan Falsafah Islam: Tumpuan Terhadap Pemikiran Fakhr al-Din al-Razi : The Creation of the Soul from the Point of View of Islamic Exegesis and Philosophy: Focus on Fakhr al-Din al-Razi’s Thought - Mohd Akib, Mohd Manawi; Ishak, Hamdi; Mohammed Zabidi, Ahmad Fakhrurrazi; Syed Muhsin, Sharifah Basirah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2023)
The soul, also known as al-nafs, is considered the second element in human beings, following the body. It plays a vital role as the overseer and administrator of every human decision and action, requiring a comprehensive understanding of its nature, potential, and ultimate happiness. In the realm of Islamic knowledge, the Qur’an serves as the primary source of reference, encompassing the discourse on al-nafs or the soul. However, this particular issue finds greater prominence within the debates of Islamic philosophers, specifically pertaining to the field of ontology. With this in mind, this article aims to examine one specific aspect of the discussion surrounding al-nafs, namely its creation, through an exploration of relevant verses from the Qur’an and insights drawn from Islamic philosophical sources. The method employed in this study involves analyzing the works of Fakhr al-Din al-Razi, including al-Tafsir al-Kabir, al-Mabahith al-Mashriqiyyah, al-Matalib al-‘Aliyah, and other significant texts representing the disciplines of exegesis and Islamic philosophy. A comprehensive understanding can be attained by examining the continuity of al-Razi’s ideas across these disciplines and comparing them with the perspectives of Abu ‘Ali al-Husayn Ibn ‘Abd Allah Ibn Sina and Abu Hamid Muhammad al-Ghazali. The findings of this article suggest that the soul, al-nafs, is a distinct entity that was created simultaneously with the body. While al-Razi’s opinion appears to align broadly with that of Ibn Sina and al-Ghazali, some shortcomings are identified within Ibn Sina’s viewpoint.